The essentially contested vocabularies related to fetal personhood - Francisco, Jose Mario C. (Philippine Studies: Historical and Ethnographic Viewpoints, 2016)
Hannah Bulloch's (2016) article is a welcome contribution to the growing volume of studies of everyday religion in both various contemporary contexts as well as earlier historical periods. These studies shift interest in social science research from institutions of religious traditions to everyday religious practices of individuals and groups within and outside such religious traditions.